Consulting to technical leaders, teams, and organizations : building leadership in STEM environments - Connell, Joanie B. (Fundamentals of consulting psychology book series., 2022)
"This book presents a rich discussion of the opportunities organizational consultants have to impact the development of technical leaders, teams, and organizations. The expansion of the tech sector has revolutionized how processes are conducted in almost every realm of industry. The role of technical leaders has evolved from supporting organizational functions to creating and leading corporations, many with worldwide impact. This boom in the technology industry has brought along unique challenges and opportunities for organizational consultants"--